Descriptive Study of Students' Knowledge, Attitudes, and Practices toward Safe Sex in Niger Delta University in, Bayelsa State, Nigeria - Ngwibete Atenchong; Folorunso Dipo Omisakin (Mashhad University of Medical Sciences, 2020)
Background & aim: Spread of sexually transmitted infections can be controlled with enhancing the knowledge and correcting the attitudes of students regarding the right and consistent use of contraceptive methods, and being in monogamous sexual relationships. This study aimed to compare thestudents' knowledge, attitudes, and safe sex practices between nursing and non-nursing undergraduate students. Methods: A descriptive survey design was employed among 240 students at Niger Delta University in Bayelsa State, Nigeria in 2018-2019 The simple random sampling technique was used to select the sample. A questionnaire designed to elicit information on knowledge, attitudes, and safe sex practices from nursing and non-nursing students. Data were analyzed using SPSS, version 17.0.  Descriptive statistic was employed to describe the data. Results: Nursing students in this study presented with safe sexual practices, compared to non-nursing students. Sexual risky behaviors, such as having a casual partner and not using condoms, were prevalent among the non-nursing students. After summing up the scores of nursing students, they showed a better understanding of knowledge of safe sex (83.1% for nursing students versus 54.6% for non-nursing students). Similarly, the nurses' attitudes and practices seemed better than those of non-nurses. Conclusion: Combination of both correct knowledge and positive attitudes correlates with safe sex practices among students. Safe sex education should be introduced to non-nursing students at the Niger Delta University as a means of promoting safe sex practices among students.